Experimental study of flow dynamics in close-coupled catalyst manifolds - Persoons, Tim (My University, 2007)
Time-resolved flow dynamics in an automotive exhaust manifold with close-coupled catalyst are investigated experimentally on a charged motored engine (CME) flow rig. Flow similarity between CME and fired engine conditions is discussed analytically. Oscillating hot-wire anemometry (OHW) is used to measure the bidirectional phase-locked velocity. Strong time-resolved mean catalyst velocity fluctuations are observed. These are analysed as Helmholtz resonances, using a one-dimensional gas dynamic model of the manifold. The spatial and temporal occurrence of instantaneous reverse flow in the catalyst is investigated, for varying engine load conditions. Periodic backflow occurs throughout large portions of the catalyst cross-section, and proves to be strongly linked to the observed Helmholtz resonances.
PUBLISHED
Keywords: Exhaust manifold; Close-coupled catalyst; Reverse flow; Helmholtz resonance; Oscillating hot-wire anemometry; Smart & Sustainable Planet